OFTEDALITE, (SC,CA,MN2+)2 K (BE,AL)3 SI12O30, A NEW MEMBER OF THE MILARITE GROUP FROM THE HEFTETJERN PEGMATITE, TøRDAL, NORWAY: DESCRIPTION AND CRYSTAL STRUCTURE - Cooper M.A.; Hawthorne F.C.; Ball N.A.; Černý P.; Kristiansen R. (My University, 2006)
Oftedalite, ideally (Sc,Ca,Mn2+)(2) K (Be,Al)(3) Si12O30, is a new mineral species from the Heftetjern granitic pegmatite, northwest of the small parish of Tordal, southern Norway. It occurs as short prismatic crystals up to 100 mu m in diameter, frequently with very thin crystals of Sc-free milarite up to similar to 10-20 mu m across in parallel orientation on the (001) faces, or as a product of replacement with other Sc-bearing minerals. Oftedalite - Sc-rich milarite is greyish white with a colorless streak and vitreous luster; it does not fluoresce under ultraviolet light. It has a poor cleavage parallel to {001}, a Mohs hardness of 6, is brittle with a conchoidal fracture, and has a calculated density of 2.614 g/cm(3). It is uniaxial negative, with epsilon 1.553, omega 1.556 (both +/-0.002), and is nonpleochroic. It is hexagonal, space group P6/mcc, a 10.097(1), c 13.991(2) angstrom, V 1235.3(6) angstrom(3), Z = 2. The strongest seven lines in the X-ray powder-diffraction pattern [d in angstrom(I)(hkl)] are: 3.229(10)(104, 211), 4.097(7)(112), 5.044(5)(110), 3.504(5)(004), 7.012(4)(002), 1.836(4)(412), 1.751(4)(008, 500), and 2.735(3) (204). A chemical analysis by electron microprobe gave SiO2 73.32, Al2O3 0.47, Sc2O3 6.77, Y2O3 0.36, FeO 0.26, MnO 1.32, CaO 4.49, K2O 4.71, BeO (calc.) 7.4 1, sum 99.11 wt.%; the Be content was determined as (3 - Al) apfu. The resulting empirical formula on the basis of 30 atoms of oxygen is (Sc0.96Ca0.79Mn0.182+Fe0.042+)(Sigma 2.00) K-0.98 (Be2.91Al0.09)(Sigma 3.0) Si-11.98 O-30. The crystal structure of Sc-rich milarite, (Sc0.84Ca1.03 Mn0.092+Y0.01Fe0.032+)(Sigma 2.00) K (Be2.86Al0.14)(Sigma 3.0) Si12O30)], very close to the ideal composition of oftedalite, was refined to an R index of 6.6% based on 430 observed reflections collected on a four-circle diffractometer with MoK alpha X-radiation and a lK CCD detector. Oftedalite is isostructural with milarite, ideally Ca-A(2) (B)square K-c (T(2))(Be2Al) ((Si12O30)-Si-T(1)) (H2O). The structure consists of a beryllo-aluminosilicate framework of the form (4(2)6(4))(4)(6(4)9(2)) in which the T(1) site is occupied by Si and forms a [Si12O30] cage, and the T(2) site is occupied by (Be + Al) and links the [Si12O30] cages into a framework. The A, B and C sites occur in the interstices of the framework with the following occupancies: A (Sc0.84Ca1.03Mn0.092+Y0.01Fe0.032+); B square; C K-1.00; T(2) (Be2.86Al0.14).
Keywords: geodesy; Oftedalite; milarite group